1976
DOI: 10.1128/iai.13.2.365-372.1976
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus mutans dextransucrase: mode of interaction with high-molecular-weight dextran and role in cellular aggregation

Abstract: The interaction between Streptococcus mutans dextransucrase (EC 2.4.1.5) and high-molecular-weight dextran was studied in both the presence and absence of substrate sucrose. Equivalent weight-percent solutions of primer dextrans that differed 200-fold in molecular weight were found to be equally efficient in priming new dextran synthesis. Sodium borohydride reduction of dextran had no effect on its priming ability. These results suggest that dextran synthesis proceeds by addition of glucosyl residues to nonred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 41 publications
6
77
0
Order By: Relevance
“…In most cases, dextran accelerates the reaction. This has been attributed to acceptor reactions, but also to the effect of dextran on the enzyme conformation, leading to modified responses to pH or to excess substrate inhibition (Côté and Robyt, 1983;Dols et al, 1997;Germaine and Schachtele, 1976;Robyt and Corrigan, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, dextran accelerates the reaction. This has been attributed to acceptor reactions, but also to the effect of dextran on the enzyme conformation, leading to modified responses to pH or to excess substrate inhibition (Côté and Robyt, 1983;Dols et al, 1997;Germaine and Schachtele, 1976;Robyt and Corrigan, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Second, glucose-grown M35 shows either no ability or a decreased ability to agglutinate upon addition of exogenous glucans such as mutan or Dextran T250 (Table 1). Some investigators have suggested that agglutination and adherence are mediated by different mechanisms (6,7,18,22,30,31,36), while others suggest that the ability of S. mutans cells to agglutinate reflects their capacity for adherence (8,15,23) and that a common mechanism governs both agglutination and adherence (26,27). Regardless of the relationship of agglutination to adherence, the strong agglutination of cells in plaque would provide tight cohesion of cells and matrix and prevent dissociation of plaque deposits by environmental factors in vitro or in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Fractions (4 ml) were eolleeted and assayed for GTF-S and GTF-I activity and absorbance at 280 nm. Fractions demonstrating GTF-S or GTF-I activity were pooled separately and eoneentrated (7,8,14). The preparations were free of fructosyltransfeiase, invertase, suerose phosphorylase and dextranase activities.…”
Section: Streptococcusmentioning
confidence: 99%
“…Assay for GTE activity. Production of glucan from sucrose by GTF-S was determined by a modification of the procedure of Germaine et al, (14). In a final volume of 450 /d, the reaction mixture contained I mM sucrose (2.5 //Ci [U-' ""C] suerose and unlabelled sucrose), 25 /Ug dextran, 70 /ig sodium fiuoride and GTF-S in a sodium acetate buffer, pH 5,5, Samples of 50 //I each were spotted onto Whatman 3 MM filter paper disks after 15 min incubation, and the disks were immediately immersed in absolute methanol.…”
Section: Streptococcusmentioning
confidence: 99%
See 1 more Smart Citation